Pengembangan Kriteria Seleksi Cabai (Capsicum annuum L.) di Lahan Gambut Provinsi Riau - Deviona; Yunandra; Wardati; Mulyani, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
The development of chili varieties tolerant to peatland is one way to increase chili production in large area peatlands. This research aimed to determine the selection criteria for tolerant chili in peatlands. The research was conducted at the Rimbo Panjang Experimental Station, Faculty of Agriculture, Riau University, from November 2020 to March 2021. This research involved 20 genotypes of nine large chilies, six curly chilies, and five bird peppers. Analysis of variance showed that the genotype had a significant effect on all quantitative characters except for harvesting date and stem diameter. The characters of plant height, canopy width, dichotomous height, fruit diameter, fruit length, fruit weight, fruit flesh thickness, flowering date, number of fruit, and fruit weight per plant had high heritability values. Path analysis showed that the fruit flesh thickness, fruit weight, fruit length, and fruit diameter directly influenced fruit weight per plant. Characters of fruit diameter, fruit length, and weight per fruit have an indirect effect on fruit weight per plant through the characteristics of fruit flesh thickness. Characters that can be used as selection criteria for peatland tolerant chili are fruit flesh thickness (0.71), fruit weight (0.80), and fruit length (0.74).Keywords: correlation, heritability, quantitative character, path analysis